ANALISIS HAMBATAN KONSEPTUAL SISWA DALAM PEMBELAJARAN MATEMATIKA BERBASIS KURIKULUM MERDEKA - Arneta, Mauda; Pujiastuti, Heni; Hendrayana, Aan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This systematic literature review aims to analyze students' conceptual barriers in mathematics learning under the Kurikulum Merdeka framework. Using the PRISMA 2020 protocol, 16 articles were selected from national and international databases based on inclusion criteria for junior and senior high school levels. The analysis reveals that conceptual barriers are dominated by three main types: ontogenic, epistemological, and didactical barriers. Although Kurikulum Merdeka emphasizes differentiated learning, it has not fully addressed these barriers due to a gap between curriculum design and classroom practice. This study recommends the development of didactical designs based on Realistic Mathematics Education (RME) and the integration of visual media and virtual manipulatives. These findings are expected to contribute to mathematics teachers' efforts in enhancing students' conceptual understanding.